NUTRIENT DIGESTIBILITY OF THE WASTE OF SACCHARIFICATION PROCESS FROM CASSAVA BAGASSE ON THE LAYING HENS - Ali-Mursyid, W.M.; Nugraha, A.S.; Zuprizal, Z. (Diponegoro University, 2011)
The objective of this research was to study the nutrient digestibility and the metabolizable energyvalue of the waste of saccharification process from cassava bagasse (WSPCB) on the laying hens.Twenty ISA-Brown laying hens at the age of 72 weeks were randomly distributed into three feedingtreatments which consisted of cassava bagase (CB), WSPCB of solid state fermentation method(WSPCB-SSF), and WSPCB of sub merged fermentation method (WSPCB-SmF). All of the hens werefasted for 24 hours and 15 of them were fed with CB, WSPCB-SSF and WSPCB-SmF (five hens foreach test-diet). The other five hens were still fasted. Then, all of the hens were fasted again and theirexcreta were collected during 48 hours. The nutrient digestibilities which were measured consisted ofthe Apparent and True Digestibility of Dry matter (ADDM and TDDM), Crude Fiber (ADCF andTDCF), Starch (ADS and TDS), and the Apparent and True Metabolizable Energy (AME and TME).The result of this research showed that the saccharification process generated the solid waste with thenutrient digestibility value (ADDM, TDDM, ADS, TDS, AME, and TME) which were significantlylower (P<0.05) than those of CB. The crude fiber digestibility value of the WSPCB has an opositephenomenon in which the ADCF and TDCF of WSPCB-SmF were greater than CB. In conclusion, thenutrient digestibility value, except for ADCF and TDCF, of the WSPCB on the laying hens were lowerin value than those CB.